Pengaruh Keadilan Distributif dan Keadilan Prosedural terhadap Kinerja dengan Kepuasan Kerja sebagai Variabel Mediasi Guru Honorer Madrasah Ibtidaiyah di Kabupaten Pacitan - Muqtafi, Faidholloh; Tjahjono, H Kurnianto; RDA, M Kurnia Puji (JUDICIOUS, 2023)
This study aims to analyze the effect of distributive justice and procedural justice on performance with job satisfaction as a mediating variable for honorary teachers at Madrasah Aliyah in Pacitan Regency. Respondents in this study were honorary teachers or non-permanent teachers at Madrasah Aliyah in Pacitan Regency, East Java. The sample used is 200 respondents, taken by saturation sampling technique. The data analysis technique used multiple regression analysis and data processing using IBM SPSS 21 software. This study found that distributive justice and procedural justice have a direct positive effect on performance. Distributive justice and procedural justice have a direct positive effect on job satisfaction. The work goals have a direct and significant positive effect on performance. The purpose of mediating the effect of distributive justice on performance. The purpose of mediating the effect of procedural fairness on performance. The difference between this study and previous research is that the object of this research is only focused on the Pacitan Regency area, while the research subjects are representatives of honorary teachers in the Pacitan Regency at the Madrasah Aliyah level. This study focuses on factors that affect performance, namely job satisfaction, procedural justice, and distributive justice. Based on this research, Kemenag or Kemendikbud Pacitan in the future can pay attention to the variables of this research aspect in the decision-making process and pay more attention to the welfare of honorary teachers. Limitations in the data collection process, the information provided by respondents through questionnaires sometimes does not show the respondent's actual opinion, this happens because sometimes there are differences in thoughts, assumptions, and different understandings of each respondent, as well as other factors such as honesty in filling out respondents' opinions in the questionnaire.